1986
DOI: 10.1210/endo-119-4-1439
|View full text |Cite
|
Sign up to set email alerts
|

Growth Factor Control of Rat Thyroid Follicular Cell Proliferation

Abstract: We have investigated the proliferative responses of rat thyroid follicular cells in serum-free culture to a range of growth factors including TSH, epidermal growth factor, and insulin, added singly or in combination. Follicles released from normal thyroids by collagenase/dispase digestion were cultured in suspension in agarose-coated microtiter plates to prevent monolayer formation. Growth responses were measured by [3H] thymidine incorporation and by autoradiography over successive 24- or 36-h periods. Insuli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
26
1

Year Published

1988
1988
1995
1995

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 75 publications
(27 citation statements)
references
References 23 publications
(21 reference statements)
0
26
1
Order By: Relevance
“…Such bell-shaped responses are a welldocumented feature of in vitro studies of cell proliferation (Bodger et al, 1979;Yen & Lewin, 1981) and have been previously reported in human thyroid follicular epithelium derived from normal glands, Graves' disease and multinodular goitre (Ollis et al, 1986) although, interestingly, not in cultures of follicular epithelium derived from other mammalian species (Roger et al, 1982;Valente et al, 1983;Smith et al, 1986).…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…Such bell-shaped responses are a welldocumented feature of in vitro studies of cell proliferation (Bodger et al, 1979;Yen & Lewin, 1981) and have been previously reported in human thyroid follicular epithelium derived from normal glands, Graves' disease and multinodular goitre (Ollis et al, 1986) although, interestingly, not in cultures of follicular epithelium derived from other mammalian species (Roger et al, 1982;Valente et al, 1983;Smith et al, 1986).…”
Section: Discussionmentioning
confidence: 79%
“…Since our previous work has always shown a close correlation between peaks of 3H-TdR incorporation, as measured by scintillation counting, and increases in the autoradiographic nuclear labelling index (Williams et al, 1987;Smith et al, 1986), the analysis of suspension cultures in this study was performed by 3H-TdR scintillation counting alone. However, all critical comparisons of growth responses were confirmed by use of autoradiographic nuclear labelling index in the monolayer cultures.…”
Section: Discussionmentioning
confidence: 95%
“…Although numerous in vitro thyroid follicular cell culture systems have been described (1,12,25,35,36,39), secretion of the thyroid hormones triiodothyronine (T3) and thyroxine (T4) is seldom measured in vitro due to the reduced ability of follicular cells growing in monolayer culture (i.e., lacking follicular organization) to concentrate and efficiently iodinate thyroglobulin. Thyroid function in vitro is often assessed by evaluating specific phases of hormone synthesis including iodide trapping (41 ); thyroglobulin expression (5, 11, 21, 24, 27, 3$), secretion (16,18), and iodination (28,33); thyroid peroxidase synthesis ( 17,44) and activity (20); and thyroid-stimulating hormone (TSH) receptor expression.…”
Section: Introductionmentioning
confidence: 99%
“…However, the growth promoting effect of TSAb or TGI remains controversial [6][7][8][9][10]. EGF or other factors such as insulin, IGF-1, or interleukin-1 also stimulate the growth of thyroid follicular cells [11][12][13][14][15][16][17][18][19][20]. Several investigators claimed that TGI was actually a contamination of EGF [8,9].…”
Section: The Growthmentioning
confidence: 99%
“…Several investigators claimed that TGI was actually a contamination of EGF [8,9]. Moreover, the signal transduction pathway of these growth factors remains unclear [3][4][5][11][12][13][14][15][16][17][18][19][20].…”
Section: The Growthmentioning
confidence: 99%